Traditional Sports Games in the Festival Culture of Tuva Turks - TÜRKMEN, Mehmet (Acta Scientiae et Intellectus, 2024)
In this study, the ‘folk games’ that are performed periodically every year in the traditional ‘Naadym’ festival of the Autonomous Republic of Tuva of the Russian Federation in Southern Siberia will be analysed. In the research, descriptive description method, which is one of the qualitative study designs, was used. The Tuvas, one of the ancient ‘nomadic’ Turkic peoples, living in the nooks and crannies of the Sayan and Altai mountains and not much affected by the pressures of globalisation, have many traditional holidays, festivals, special family or tribal ceremonies, as well as a large number of traditional (folk) games and competitions in their organisation. In this research, we focused on the official holiday of the Tuvans Naadym, and the traditional side of the folk dances performed here, as it is the most stable and has stood the test of time. We tried to explain the folk dances of the Naadym holiday and their sign character in the context of the traditional festive culture of the Tuva people. Conclusion: Tuva people’s festive celebrations and traditional dances retain their national and religious character - although half of the population is Buddhist, Buddhism elements are only a veneer - elements of Shamanism, their ancient religion, lie at the core of the inner and outer lines of the dances; they insist on keeping the elements of traditional culture alive.